A PERISCOPE INTO THE PSYCHO-SOCIAL AND ECONOMIC CHALLENGES EXPERIENCED BY FAMILIES OF PERSONS WITH MENTAL DISORDERS IN KADUNA STATE - FARIDA ABUBAKAR SAULAWA (International Studies Journal)
Mental health is important at every stage of life, ranging from childhood and adolescence through adulthood. It is as important as physical health to daily living -- a relative state of mind in which a person who is healthy is able to cope with and adjust to the recurrent stresses of everyday living. This study adopted mixed methods, where other related studies adopted one method, utilizing both in-depth interviews and questionnaires, which comprised of a total of four hundred (400) caregivers who have consistently accompanied their mentally ill patients to the hospital in the last six months. The data revealed families of people with mental disorders face a variety of challenges, including: psychological, emotional, financial, and social challenges. Family members often experience disturbing thoughts, emotional disturbance, communication problems, and worry about the future. They may also experience depression, anxiety, sadness, guilt, and sometimes shame. Equally, in the social front, the caregivers experience discrimination, stigma and lack of social support from relatives, the community and the government, thereby leading to increased social distance. Economic challenges are also a problem as the families experience financial constraints emanating from costs for patient care and transportation, and shortages of medicine. Most of them struggle with poverty and interference with income generating activities. In order to address the psycho-social challenges of families caring for their relatives suffering from mental illness in Kaduna state, this research recommends, that families of patients with mental disorders should have better access to financial assistance and psychological support. The federal government in collaboration with non-governmental organizations (NGOs) could provide funding to ease the financial burden and mental health services for caregivers. There is also the need for improved mental health education. This study tend to cover the gap where much has not been done in the northern region concerning care for mental health patients and specifically no single published research on the challenges of caring for mental health patients in the study area.